HARMONIZING NATIONAL AND SCIENTIFIC VALUES AGAINST THE INFLUENCE OF MASS CULTURE (World Conference on Social Sciences, Law and Public Policy, 2026)
This article examines how national and scientific values can be harmonized to counter the homogenizing and often destructive influence of mass culture on youth in New Uzbekistan. Mass culture, amplified by digital media and globalization, reshapes worldviews, weakens historical memory and national identity, and promotes consumerism and superficiality. At the same time, the national idea, cultural heritage, and scientific–rational thinking offer powerful resources for building critical media literacy, spiritual immunity, and value-oriented modernization. Using a socio-philosophical and pedagogical approach grounded in Uzbek and regional scholarship, the article analyzes the risks of uncontrolled mass culture, conceptualizes the relationship between national and scientific values, and proposes a model for integrating them in education, media policy, and youth work. The findings suggest that value-based education, creative use of technology, and the Jadid legacy can transform mass culture from a threat into a medium for national and intellectual renewal.
Keywords: mass culture, national values, scientific values, youth worldview, New Uzbekistan, Jadids, media literacy, spiritual immunity, globalization, national idea